Dinitrosylbis[tris(4-fluorophenyl)phosphane]iron chloroform monosolvate - Jones, Myron W. (International Union of Crystallography, 2011)
The title compound, [Fe(NO)(2)(C(18)H(12)F(3)P)(2)]·CHCl(3), belongs to the family of metal dinitrosyl compounds with the general formula Fe(NO)(2)(L)(x), referred to collectively as ‘dinitrosyl iron compounds’ (DNICs). Herein we report the structure of a dinitrosyl iron diphosphane complex, (Fe(NO)(2) L (2), with L = P(C(6)H(4)-p-F)(3). The structure includes one metal complex molecule and one chloroform solvent molecule. The iron atom is tetrahedrally coordinated with two phosphane ligands and with two NO groups with Fe—N—O angles of 178.1 (2) and 177.0 (2)°.